Attitudes and perceptions regarding entrepreneurship around the world : a cluster analysis approach - Nunes, Alcina (2014)
Nowadays it is believed that entrepreneurship could be a driving force in growth and development. For the achievement of a relevant national entrepreneurship rate the social and economic business environment can be crucial. However, despite the international attention given to entrepreneurship, it is not known if it is a global phenomenon or if there are particular regions where the entrepreneurial activity is specially recognized by society. Applying cluster analysis statistical techniques to a dataset gathered by the Global Entrepreneurship Monitor (GEM) and that includes, in 2010, 59 countries this paper intends to identify groups of countries with the same population attitude and perception regarding entrepreneurship.